2018
DOI: 10.15282/jmes.12.4.2018.12.0358
|View full text |Cite
|
Sign up to set email alerts
|

The potential effectiveness of lean construction principles in reducing construction process waste: an input-output model

Abstract: With the spread of a culture of waste reduction in the construction industry, the traditional management system has become insufficient, so it has become crucial to implement more innovative techniques to improve the performance of this sector. In response to this need, Lean Construction (LC), which is the global reference of a production system with the minimum of waste generation, has attracted several construction companies all over the world. However, previous studies indicate that are several implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Likewise, the commonsenseconnectionsbetweenthosestandardsandnine sources of waste have been examined [2]. Bogdan Bahnariu(2018) has studied the hurdles and success factors which would permit to create and executethe Lean culture important to empower Lean management tools.…”
Section: Ms Bajjou and A Chafi(2018)mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the commonsenseconnectionsbetweenthosestandardsandnine sources of waste have been examined [2]. Bogdan Bahnariu(2018) has studied the hurdles and success factors which would permit to create and executethe Lean culture important to empower Lean management tools.…”
Section: Ms Bajjou and A Chafi(2018)mentioning
confidence: 99%
“…The placement of the belongings the capacity as to how much work can be extracted out of it and at what levels one canprovidecustomersatisfactioniswhatleanconstructionis all about. Lean development comprehends the weakness in stocks and consider cost as the key prospect and deploy constructionwithaneedtoproceedtheworktothenextgroup and after that it is brainstormed to come up with different opinions [2].…”
Section: Introductionmentioning
confidence: 99%
“…Limited previous models concerning LC were developed, but most of them do not refer to LC evaluation. A lean model based on six main principles was developed by Bajjou and Chafi (2018). Client Focus, Waste Consciousness, Quality, Material flow and pull, Organization/ planning /info flow, Continuous improvement, Kaizen were the identified principles.…”
Section: Introductionmentioning
confidence: 99%
“…Seven LC principles were summarized in an understandable model, to assess the consciousness of the LC principles among Malaysian construction companies. The summarized principles were: Specify value, Identify and map the value stream, Flow, Pull, Perfection/continuous improvement, Transparency, Process variability (Bajjou & Chafi, 2018). Nascimento et al (2017) developed and applied a new model namely Digital Obeya Room (DOR) that demonstrated the interactions between Building Information Modeling (BIM) and lean prin ciples to improve workflows, data analysis, and 3D visual management of construction planning and control.…”
Section: Introductionmentioning
confidence: 99%
“…Lean construction's response to the construction industry production variability is to create a practical solution, the Last Planner System (LPS). LPS have generated a complex web of integrated tools and solutions that in turn has created a problem of how to implement it [7] [8].…”
Section: Introductionmentioning
confidence: 99%